Knuth Morris Pratt String Matching Algorithm in Searching for Zakat Information and Social Activities - Riawan, Fendi; Hariguna, Taqwa (Bright Publisher, 2022)
Algorithms are one of the components that need to be considered in the development of information systems. Determination of the algorithm is adjusted to the purpose of the system to be built. One algorithm that can be used is string matching. The string matching algorithm will play a role in searching for a string consisting of several characters (usually called a pattern). The method used in this research is string matching knuth morris pratt (KMP) which is used to search zakat information and social activities in the search engine system. KMP is a string matching algorithm with good performance. The results showed the performance of string matching using the KMP algorithm with 5 trials of input pattern on zakat information with execution times of 0.03 ms, 0.03 ms, 0.02 ms, 0.02 ms and 0.03 ms. And 5 times the input pattern experiment on social activities with execution time of 0.02 ms, 0.02 ms, 0.03 ms, 0.03 ms and 0.02 ms. Thus the average execution time of the KMP algorithm in string matching is 0.026 ms and 0.024 ms.